Sex differences in electrolyte imbalances caused by SARS‐CoV‐2: A cross‐sectional study. Issue 12 (6th October 2021) - Pani, Arianna; Inglese, Elvira; Puoti, Massimo; Cento, Valeria; Alteri, Claudia; Romandini, Alessandra; Di Ruscio, Federica; Senatore, Michele; Moreno, Mauro; Tarsia, Paolo; Colombo, Fabrizio; Epis, Oscar Massimiliano; et al.
Abstract: Background: Since SARS‐CoV‐2 spread, evidence regarding sex differences in progression and prognosis of COVID‐19 have emerged. Besides this, studies on patients' clinical characteristics have described electrolyte imbalances as one of the recurrent features of COVID‐19. Methods: We performed a cross‐sectional study on all patients admitted to the emergency department (ED) from 1 March to 31 May 2020 who had undergone a blood gas analysis and a nasopharyngeal swab test for SARS‐CoV‐2 by rtPCR. We defined positive patients as cases (n = 710) and negatives as controls (n = 619), for a total number of patients of 1.329. The study was approved by the local ethics committee Area 3 Milan. Data were automatically extracted from the hospital laboratory SQL‐based repository in anonymised form. We considered as outcomes potassium (K + ), sodium (Na + ), chlorine (Cl − ) and calcium (Ca ++ ) as continuous and as categorical variables, in their relation with age, sex and SARS‐CoV‐2 infection status. Results: We observed a higher prevalence of hypokalaemia among patients positive for SARS‐CoV‐2 (13.7% vs 6% of negative subjects). Positive patients had a higher probability to be admitted to the ED with hypokalaemia (OR 2.75, 95% CI 1.8‐4.1, P < .0001) and women were twice as likely to be affected than men (OR 2.43, 95% CI 1.67‐3.54, P < .001). Odds ratios for positive patients to manifest with an alteration in serum Na + was (OR 1.6, 95% CI 1.17‐2.35, P < .001) and serum chlorine (OR 1.6, 95% CI 1.03‐2.69, P < .001). Notably, OR for positive patients to be hypocalcaemic was 7.2 (95% CI 4.8‐10.6, P < .0001) with a low probability for women to be hypocalcaemic (OR 0.63, 95% CI 0.4‐0.8, P = .005). Conclusions: SARS‐CoV‐2 infection is associated with a higher prevalence of hypokalaemia, hypocalcaemia, hypochloraemia and sodium alterations. Hypokalaemia is more frequent among women and hypocalcaemia among men.